Automated Acquisitions: Issues for the Present and Future, 1st edition - Dykeman, Amy (Routledge, 2020)
In this book, first published in 1989, practicing librarians share their hands-on experience with implementing various types of acquisitions systems and address planning considerations, the blurring of roles between acquisitions and cataloguing, staffing implications, electronic record transmission, and specialized functions of automated acquisitions systems. These librarians reveal what they wish they knew when they began to implement their systems, as well as what went right - and wrong - along the way. Acquisitions librarians, systems librarians, and any professionals planning for an automated acquisitions system in their libraries will not want the miss the underlying excitement expressed by contributors as they re-evaluate acquisitions work and redefine the role of the acquisitions librarian as a result of automated acquisitions systems.